Quality of life of caregivers of elderly people with stroke at the hospitalization time and after leaving hospital, and its association with patients disabilities - baghcheghi, nayereh; koohestani, hamidreza (Advances in Nursing & Midwifery, 2012)
Abstract Background and aim A large proportion of stroke patients are maintained at home by their family. This study was conducted to evaluate life quality of caregivers of stroke patients after discharge period and its association with patient dependency in performing daily activities. Materials and methods This research is a descriptive study. A sample of 90 stroke patients hospitalized in Arak teaching hospital and care-givers were selected with convenience sampling method. By using a questionnaire, samples were collected, three times, at the time of discharge, also one month and three months after discharge. Quality of life was measured with brief quality of life questionnaire Of WHO. Then, quantity of patient dependency in performing daily activities was measured by using the Modified Barthel Index (MBI). Results Most of the care-givers were the spouse of the patient (77.77%) and the average age of them was 60.1 years old. After 1 and 3 months, their quality of life in four-domain (psychological and physically health, social relations and environment health) were significantly decreased. There was significant relationship between quality of life of caregivers and quantity of patients dependency in performing daily activities. Scores average and scale deviation (SD) of patients (Barthel patients) had no significant difference at the time of discharge, also one month and three months after discharge. Conclusion Quality of life of caregivers of stroke patients after discharge was decreased and was related to patient dependency in performing daily activities. Results indicated that caregivers of stroke patients need help and support to adapt to changes in lifestyle. Key words: quality of life, caregiver, stroke, patient dependency